Arterial Spin Labeling MRI to Measure Cerebral Blood Flow in Untreated Ischemic Stroke. Issue 2 (9th October 2018) - Crisi, Girolamo; Filice, Silvano; Scoditti, Umberto
ABSTRACT: BACKGROUND AND PURPOSE: This study aims to investigate the significance of regional hyperperfusion (RH) detected by arterial spin labeling (ASL) in a group of untreated stroke patients, within 24‐36 hours after symptom onset. The relationship between RH volume and infarcted volume (DIV) as defined on diffusion weighted images (DWIs) was evaluated. METHODS: Of the 346 consecutive acute stroke patients who attended our center, we retrospectively reviewed MRI studies of 47 patients who were ineligible for standard treatment with intravenous tissue plasminogen activator. The MRI study included ASL and DWI. The ASL‐derived cerebral blood flow (CBF) maps were coregistered on the DWI images. RH volume and DIV were calculated and compared. Patient NIHSS scores were also evaluated at admission, discharge, and after 1 and 6‐month follow‐up. RESULTS: Twenty‐two patients showed RH with CBF twice than baseline. In all 22 patients, RH overlaps with DWI infarcted area. No significant difference ( P = .94) between RH volume and DIV was found (7.2 ± 9.6 and 9.0 ± 11.9 cm 3 ). The Pearson's correlation coefficient between RH and DIV was .93. On univariate analysis, a significant difference was found between patient's groups on NIHSS at any time points, after covariates adjustment NIHSS difference was significant only at admission. CONCLUSIONS: The study showed that ASL perfusion could be an integral part of the MRI examination in the assessment of 24‐36 hours not‐treated stroke patients as sustained RH group had improved outcomes. More importantly, ASL perfusion may provide evidence of beneficial effects of reperfusion induced by recanalization treatment.